Questionnaire on ageing: education, work, social security and justice - Ecuador. Defensoría del Pueblo (Quito: DPE, 2019)
The Office of the Ombudsman of Ecuador (DPE, for its acronym in Spanish), within the framework of its competences, sends this document in response to the request for information sent by the Chairman of the Open-ended Working Group on Ageing. This document analyses some of the requested aspects regarding the following topics: 1) Education, training, lifelong learning and capacity building 2) Social protection and social security; 3) Right to work and access to the labour market; and, 4) Access to justice. It should be noted that this questionnaire is partially answered within the framework of the Ombudsman's competence.